Selected flavonoid compounds as promising inhibitors of protein kinase CK2α and CK2α′, the catalytic subunits of CK2. (April 2017) - Baier, Andrea; Galicka, Anna; Nazaruk, Jolanta; Szyszka, Ryszard
Abstract: CK2 is a ubiquitous protein kinase involved in many cell functions. During the last years it became an interesting target in cancer research. A series of flavonoid compounds was tested as inhibitors of protein kinase CK2. Several substances were found to be highly active against both catalytic subunits with IC50 values below 1 μM in case of CK2α′. The most promising inhibitor we identified is chrysoeriol with IC50 values of 250 and 34 nM for CK2α and CK2α′, respectively. Graphical abstract: Several flavonoid compounds were tested as potential protein kinase CK2 inhibitor. We identified several substances decreasing the phosphorylating activity. The most promising inhibitor was chrysoeriol (1 ). Highlights: Several flavonoid compounds are potent CK2 inhibitors. In most cases the CK2α′ subunit is more effective inhibited than CK2α. Chrysoeriol was identified as a new and very promising CK2 inhibitor.